RETENSI PENGETAHUAN TUMBUHAN PANGAN SUKU REJANG DI KAMPUNG RINDU HATI DALAM KETAHANAN PANGAN - Zikri, Merlian; Hikmat, Agus; Zuhud, Ervizal A. M. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Development direction of Indonesia's food security today by reviving food diversity by raising the